Effect of Different Pre-treatments on Seed Germination in Adenanthera pavonina L. - Paneru, Yagya Raj; Chalise , Pratikshya; K.C., Amrit (Journal of Plant Resources, 2024)
Adenanthera pavonina L. is an important medicinal plant with colorful seeds. The hard seed coat that covers the seeds causes them to go dormant. This study aimed to compare how various pretreatment techniques affected the germination percentage and mean germination time in A. pavonina. The pretreatments involve scraping seeds with sandpaper, immersing seeds in sulphuric acids for 10 minutes and boiling for ten minutes. The findings indicate that the pre-treatments have significant effect on rate of germination. The seeds that were scraped had the highest germination rate (78.33%) and the least mean germination time (6.91 days), followed by acid treatment (68.33%, 16.6 days). However, the seeds treated with boiling water showed the least germination (42.5%, 22.40 days). Environmental conditions like light and darkness did not show significant effect on rate of germination for large-scale seed germination, acid treatment like immersing in sulphuric acid can effectively increase the rate of germination and shorten the germination period because scraping takes a long time for an enormous quantity of seeds.